2021
DOI: 10.1177/00258172211042699
|View full text |Cite
|
Sign up to set email alerts
|

Consent for septoplasty: Are we meeting patients’ expectations?

Abstract: The requirements for informed consent were modified in 2015 following the UK Supreme Court judgment of Montgomery v Lanarkshire Health Board. This marked a decisive shift from the traditional paternalistic ‘doctor knows best' model towards a more patient-centred approach. This study examines the current standard of consent for septoplasty and whether it complies with the law. We also report whether the ‘reasonable patient’ and surgeon agree about which risks should be discussed during the consent process. Ten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…How the surgical problem is communicated to the patient and how the patient perceives the message from the surgeon has not been well studied, but it could be a potentially important factor for success. In particular, the issue of possible complications of septoplasty appears to have been left out of the patient information ( 5 ). This discussion could also include objective and documented preoperative information such as rhinomanometry results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…How the surgical problem is communicated to the patient and how the patient perceives the message from the surgeon has not been well studied, but it could be a potentially important factor for success. In particular, the issue of possible complications of septoplasty appears to have been left out of the patient information ( 5 ). This discussion could also include objective and documented preoperative information such as rhinomanometry results.…”
Section: Discussionmentioning
confidence: 99%
“…It also gives the patient a negative impression of a surgical complication having occurred. In a study from England where both ENT surgeons and patients were asked if they addressed these complications prior to surgery it was shown that not all of the most common complications were discussed and furthermore, surgeons and patients do rate their severity differently ( 5 ). For example, pain was among the complications not discussed with the patients routinely, which could have a negative impact once it occurs .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study exploring the consent process in septoplasty found that a significant proportion of ENT surgeons do not meet patients' expectations regarding risk disclosure for similar reasons. 15 In addition, a few ENT surgeons specifically did not consent for damage to the nasolacrimal duct because they felt it should never occur during routine FESS. These explanations, whilst possibly meeting the Bolam test, fail to adhere to the new legal standard defined by the 'Montgomery v Lanarkshire Health Board' case.…”
Section: Discussionmentioning
confidence: 99%